The discharge condition to enhance electron density of capacitively coupled plasma with multi-holed electrode - Lee, HunSu; Lee, YunSeong; Chang, HongYoung (AMER INST PHYSICS, 2012)
The multi-holed electrode that has been reported to enhance the electron density of the capacitively coupled plasma is now being adopted to speed up the processes. However, the discharge condition when the multi-holed electrode enhances the electron density of the discharge at fixed power is not studied. At low pressure, the multi-holed electrode increased the electron density of the plasma at fixed power. However, the multi-holed electrode is experimentally revealed to lower the electron density at high pressure. In this paper, the different roles of the multi-holed electrode are experimentally studied. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4748576]
Keywords: LARGE-AREA; FREQUENCY; ARGON; FILM